Emergency surgical workload in a teaching hospital - Bhattarai, P (Journal of Institute of Medicine Nepal, 2010)
Introduction: Emergency operations are life saving and it may account for over 50% of surgical admissions depending upon the place. Its impact on the skill development in a teaching hospital is very important. However the impact on service provision and implications for training are difficult to quantify. We analyzed ten months data of emergency operations done at Kohalpur Teaching Hospital. Methods: Data on emergency surgical operations over twelve months was collected including patient demographics, diagnosis, and operation and analyzed according to the operation performed and age-groups. Results: There were 535 emergency surgical operations over ten months; 20.7% were under 14 years of age, 48.7% were between 15-39 years of age and 30.4% patients were more than 39 years age. The commonest operations performed were from gastrointestinal cases (38.6%), orthopedic (21.4%), and wounds (20.5%). Conclusions: Children constituted one fourth of the total operations indicating peripheral hospital should have provision of a paediatric surgical team to have the optimum service. Resource planning should be based on more comprehensive, prospective data such as these. DOI: http://dx.doi.org/10.3126/joim.v32i1.3998 Journal of Institute of Medicine, April, 2010; 32:1 pp.31-33